2020
DOI: 10.3390/fermentation6010019
|View full text |Cite
|
Sign up to set email alerts
|

Cheese Whey Fermentation by Its Native Microbiota: Proteolysis and Bioactive Peptides Release with ACE-Inhibitory Activity

Abstract: Cheese whey contains about 20% of the total milk protein and has high nutritional and technological value, as well as attractive biological properties. Whey protein represents an important source of bioactive peptides with beneficial effects on health (e.g., antioxidant, antidiabetic, antihypertensive, etc.). Microbiota in cheese whey can hydrolyze proteins and generate bioactive peptides through a fermentation process. The objective of this study was to evaluate the effect of temperature on the fermentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
6
43
1
Order By: Relevance
“…This practice is considered economically disadvantageous due to storage and transportation costs. Considering that acid whey retains about 50% of the original nutrients of milk (e.g., lactose, protein, minerals, and fat), it should be converted into valuable co‐products by diverse technological processes (Mazorra‐Manzano et al., 2020). One of the most common ways of valorizing whey in small dairy plants is thermo‐coagulation (Fox et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This practice is considered economically disadvantageous due to storage and transportation costs. Considering that acid whey retains about 50% of the original nutrients of milk (e.g., lactose, protein, minerals, and fat), it should be converted into valuable co‐products by diverse technological processes (Mazorra‐Manzano et al., 2020). One of the most common ways of valorizing whey in small dairy plants is thermo‐coagulation (Fox et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cheese whey, the byproduct of cheesemaking, is relatively nutritious as the whey retains approximately 55% of the original milk nutrients such as fat, lactose, protein, and minerals. Many studies have shown that the resultant peptides from whey fermentation using either bacterial or fungal proteases possess various bioactivities (Brandelli et al., 2015; Mazorra‐Manzano et al., 2020; Skrzypczak et al., 2019; Welsh et al., 2017). A recent report made by Worsztynowicz et al.…”
Section: Sourcesmentioning
confidence: 99%
“…The bioactive compounds are synthesized and secreted into the culture medium by the fermenting organisms during the process. SmF has been employed to ferment many food sources to obtain BPs, including cheese whey, mushroom, tomato pomace, and feather keratin (Mazorra-Manzano et al, 2020;Mechmeche et al, 2019;Moayedi et al, 2016Moayedi et al, , 2018Worsztynowicz et al, 2020;Wu et al, 2019). Several critical factors, including optimal operating conditions, substrates, and microorganisms used, should be considered during food fermentation for the production of BPs (Lasrado & Rai, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whey protein affects satiation through the action of either intact whey protein fractions, bioactive peptides derived from whey, amino acid products of its digestion, and the combined action of whey protein or its products with other milk constituents [ 65 ]. Bioactive peptides from whey released during food processing (by enzymatic hydrolysis or fermentation) or during gastrointestinal digestion have received particular interest due to their anti-hypertensive and opioid activity [ 66 , 67 , 68 ]. Casein is another abundant milk protein known for its beneficial role in the regulation of food intake, postprandial glycaemia, and enteroendocrine hormone secretion.…”
Section: Food-derived Bioactive Molecules As New Active Compounds mentioning
confidence: 99%